Spatial distribution and abundance of Channa striata Bloch1793 in Sempor Reservoir, Kebumen Central Java - Setyaningrum Nuning (EDP Sciences, 2021)
Channa striata are one of the essential catches in freshwater, including Sempor Reservoir. This study aimed to investigate the spatial distribution and abundance of Channa striata and the correlation between the abundance of snakehead and water quality parameters. The study was undertaken in Sempor Reservoir Central Java from March to October 2020. The method included a survey with five Stations of sampling. Distribution data were tabulated using the Microsft Excel program. Data of abundance and water quality were subjected to ANOVA. The correlation between the abundance and water quality was analyzed with the Principle Component Analysis (PCA). The result showed that the distribution of snakehead fish in Sempor Reservoir covered a wide range across the inlets, middle, outlets, and beyond the dam. The catch fish was 110-390 mm long and weighed 12-588g. The male and female fish percentage was 55.68% vs 44.32%, so the female to male ratio was 0.8:1. The highest abundance of snakehead fish was in the KW station (33%). The distribution of C.striata was more affected by the fish behaviour in selecting their habitat than the water temperature, depth, and transparency. The significance of this study expects to lay the foundation for snakehead fisheries management in Sempor Reservoir.